DESIGN, SYNTHESIS, AND CHARACTERIZATION AND BIOLOGICAL STUDIES OF SOME BENZIMIDAZOLE DERIVATIVES (International Journal of Food and Nutritional Sciences, 2022)
Breast cancer is individual of the most vital types of cancer, leading to deaths in the majority of the female population. Globally, various synthetic compounds are being researched for effective treatment and management of breast cancer. In this category, benzimidazole has received the most attention. The present study was carried to synthesis 12-benzimidazole compounds were screened for in vitro anticancer activity against the MCF-7 cancer cell line. A molecular docking study was performed on the data set using gold software (PDB code: 1ZXM) as a possible target for anticancer activity. Molecular docking results showed that compounds N1, N5, N7, N9, and N12 showed good docking scores with better interaction within key amino acids, which correlated with their anti-cancer results. The synthesised molecules were validated using NMR, mass spectrometry, FT-IR, and physicochemical properties. A selected dataset of synthesised benzimidazole compounds was evaluated for their in vitro anticancer activity against cancer cell lines (MCF-7) using the 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay. The anticancer activity of all the synthesised compounds was carried out by the in vitro method to determine the IC50 value. From the results of anticancer activity, compound N10 showed higher sensitivity and a better IC50 value in the range of 7.48 μM MCF-7 cancer cells compared to the standard drug doxorubicin (IC50: 7.90 μM). The ADME results showed that compounds N1, N9, and N12 have significant results in close agreement with Lipinski's rule of five and the Qikprop range rule, and these compounds can be taken as lead molecules for the discovery of new anticancer agents.